Identification of Novel F9 Gene Variants in 143 Vietnamese Patients with Hemophilia B - Bach KQ; Duong CQ; Vu HTB; Nguyen BTN; Nguyen TT; Nguyen MT; Li R; Hutchison W; Esaq FS; Tran H; Nguyen TH (Journal of Blood Medicine)
Khanh Quoc Bach,1– 3 Chinh Quoc Duong,1,2 Huong Thi Bich Vu,1 Binh Thanh Ngoc Nguyen,1 Trang Thuy Nguyen,1 Mai Thi Nguyen,1 Ruoxin Li,4 Wendy Hutchison,4 Farisha Shabnam Esaq,4 Huyen Tran,5 Thanh Ha Nguyen1,3 1National Institute of Hematology and Blood Transfusion, Hanoi, Vietnam; 2University of Medicine and Pharmacy, Vietnam National University, Hanoi, Vietnam; 3Hanoi Medical University, Hanoi, Vietnam; 4Thalassemia and Haemophilia Molecular Reference Laboratory, Monash Medical Centre, Melbourne, Victoria, Australia; 5Haemophilia Treatment Centre, Australian Centre for Blood Diseases, Monash University, Melbourne, Victoria, AustraliaCorrespondence: Thanh Ha Nguyen, National Institute of Hematology and Blood Transfusion, No. 5 Pham van Bach Street, Cau Giay District, Hanoi, Vietnam, Email nguyenhathanh@hmu.edu.vnPurpose: Vietnam is estimated to have approximately 30,000 hemophilia B (HB) carriers, with hundreds of new cases registered annually. However, comprehensive molecular studies on HB remain limited. Therefore, this study aimed to characterize genetic variants and assess their clinical significance in unrelated Vietnamese patients with HB.Patients and Methods: This study included a cohort of 143 unrelated HB patients with diagnosed FIX levels. Genetic analysis of the F9 gene was performed using DNA sequencing and other molecular techniques. Variant pathogenicity was classified following ACMG/AMP guidelines, supplemented by computational predictions and clinical data.Results: A 100% variant detection rate was achieved, identifying 83 unique variants from 143 patients. Single nucleotide variants were predominant, with missense variants accounting for 71.08%. Of the 83 unique variants, 20 novel variants were identified, including six missenses, four nonsenses, four frameshifts, two large deletions, two in-frame deletions, and two splice-site variants. The serine protease domain contained the highest proportion of variants (49.4%). Pathogenicity analysis revealed a predominance of severe phenotypes (72.03%). Among the novel variants, twelve were classified as pathogenic, one as likely pathogenic, and seven as variants of uncertain significance. A noteworthy case was the NM_000133.4:c.-21C>T promoter variant associated with HB Leyden, which demonstrated age-dependent improvements in factor IX levels.Conclusion: This study expands the mutational spectrum of HB in the Vietnamese population and provide critical insights into genotype-phenotype correlations. The identification of novel variants enhances diagnostic precision and underscores the importance of comprehensive genomic analyses in understanding disease mechanisms. Keywords: factor IX, bleeding disorder, blood disease, next-generation sequencing, genetic disease, coagulation factor